Reconfigurable context reactive blended networking and communication courses - Huggard, Meriel; Mc Goldrick, Ciaran (My University, 2020)
This white paper briefly documents the authors’ experiences in developing and delivering graduate level educational experiences and outcomes in courses substantially built around computer networking content and principles - through traditional academic, blended and wholly online delivery and engagement modalities. The approach, strategies and content have been developed, delivered and refined over multiple presentations, and have been validated with class sizes of over 100 full-time students per presentation.Efficacious graduate education is, of necessity, both individual and collective in scope and nature. A key, perhaps indispensable,component of the nurturing and development of many core graduate attributes is the nature and quality of the mentor/apprentice learning, experience, and interactions that are both mandated and organically fostered during this time. Encapsulating and validating these facets in blended learning or wholly online settings is at the core of this discussion paper.The approach, concepts and principles also translate readily to senior undergraduate settings, and were successfully employed in a pandemic-inspired Innovative Networking solutions challenge that ran in March and April 2020.
ACM SIGCOMMEDU Workshop
Keywords: Reactive blended networking; Communication; Reconfigurable context